Health services reform in Bangladesh: hearing the views of health workers and their professional bodies - Cockcroft Anne; Milne Deborah; Oelofsen Marietjie; Karim Enamul; Andersson Neil (BMC, 2011)
Abstract Background In Bangladesh, widespread dissatisfaction with government health services did not improve during the Health and Population Sector Programme (HPSP) reforms from 1998-2003. A 2003 national household survey documented public and health service users' views and experience. Attitudes and behaviour of health workers are central to quality of health services. To investigate whether the views of health workers influenced the reforms, we surveyed local health workers and held evidence-based discussions with local service managers and professional bodies. Methods Some 1866 government health workers in facilities serving the household survey clusters completed a questionnaire about their views, experience, and problems as workers. Field teams discussed the findings from the household and health workers' surveys with local health service managers in five upazilas (administrative sub-districts) and with the Bangladesh Medical Association (BMA) and Bangladesh Nurses Association (BNA). Results Nearly one half of the health workers (45%) reported difficulties fulfilling their duties, especially doctors, women, and younger workers. They cited inadequate supplies and infrastructure, bad behaviour of patients, and administrative problems. Many, especially doctors (74%), considered they were badly treated as employees. Nearly all said lack of medicines in government facilities was due to inadequate supply, not improved during the HPSP. Two thirds of doctors and nurses complained of bad behaviour of patients. A quarter of respondents thought quality of service had improved as a result of the HPSP. Local service managers and the BMA and BNA accepted patients had negative views and experiences, blaming inadequate resources, high patient loads, and patients' unrealistic expectations. They said doctors and nurses were demotivated by poor working conditions, unfair treatment, and lack of career progression; private and unqualified practitioners sought to please patients instead of giving medically appropriate care. The BMA considered it would be dangerous to attempt to train and register unqualified practitioners. Conclusions The continuing dissatisfaction of health workers may have undermined the effectiveness of the HPSP. Presenting the views of the public and service users to health managers helped to focus discussions about quality of services. It is important to involve health workers in health services reforms.